PENGARUH MEKANISME GCG TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI - Ibrahim Dhia Furqoni; Dwi Ratmono (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of good corporate governance (GCG) influence on a company’s financial performance (FP) by mediating earnings management (EM) using the Modified Jones Model (1995). The dependent variable in this study is financial performance. The independent variable used is the mechanism of GCG. This study also uses mediation variables, that is earning management.The sample of this study consisted of 68 manufacturing sector companies listed on the Indonesia Stock Exchange in 2016-2019 so that the total sample of the study was 272. The data used in this study were secondary data and sampling using a purposive sampling method. The analysis technique used to test the research hypothesis is the Partial Least Square - Structural Equation Model (PLS-SEM) in the SmartPLS 3.0. The results of this study indicate that GCG and FP has no significant effect on Earning Management. And also, earnings management doesn’t mediate between GCG and financial performance. While GCG has a positive significant on the company's financial performance.